A foggy notion [solar photovoltaic power system]. - Goldstein, H. (IEEE spectrum)
When completed, the Bavarian Solarpark will count as one of the largest photovoltaic power plants in the world. With 57,600 solar panels covering a total of 25 hectares of farmland, the 10-megawatt peak station actually consists of three collector installations located within a 50 km radius. While the plant is expected to partially replace Germany's nuclear and fossil fuel power plants with homegrown solar PV plants, the losses due to transmission of central station solar power negate the benefits enjoyed by users of on-site solar generation. The ultimate goal, however, is to foster the growth of a global PV industry and to count on economies of scale to bring the price of PV down to levels that even developing countries can afford.